The country where my heart is : historical archaeologies of nationalism and national identity - Brooks, Alasdair Mark; Mehler, Natascha (University Press of Florida, 2017)
This international volume analyzes the archaeology of the period when modern national identities were initially formed and political nationalism was developed. Using the Peace of Westphalia (1648) and the beginning of the French Revolution (1789) as temporal bookends, the contributors view the concept of national identity as distinct from race and ethnicity.